The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4088/jcp.13r08815
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation for Treatment-Resistant Depression

Abstract: For MDD patients with 2 or more antidepressant treatment failures, rTMS is a reasonable, effective consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
174
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(186 citation statements)
references
References 40 publications
3
174
0
3
Order By: Relevance
“…A meta-analysis found that rTMS is as effective as atypical antipsychotics (same NNT) in treatment-resistant depression (Gaynes et al 2014), while other meta-analysis suggested that rTMS has the same effi cacy of commonly available antidepressant drugs in depression (Schutter 2009). A recent meta-analysis suggested that ECT seems superior to rTMS, although the quality of the included studies was low (Ren et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis found that rTMS is as effective as atypical antipsychotics (same NNT) in treatment-resistant depression (Gaynes et al 2014), while other meta-analysis suggested that rTMS has the same effi cacy of commonly available antidepressant drugs in depression (Schutter 2009). A recent meta-analysis suggested that ECT seems superior to rTMS, although the quality of the included studies was low (Ren et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) is an effective treatment for medication-refractory major depressive disorder [1], yet the mechanisms of action for this intervention are poorly understood. Studies have shown that rTMS treatment for depression may be associated with changes in serum markers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review revealed that rTMS is an effective antidepressant treatment for adolescents with resistant depression (Donaldson et al, 2014). Although studies have found that the effectiveness of rTMS for some patients with depression is not obvious (Couturier, 2005), several randomized, controlled trials have reported that rTMS is effective in the treatment of depression or treatment-resistant depression (Berlim et al, 2011;Gaynes et al, 2014). Animal research has revealed that chronic rTMS increases hippocampal neurogenesis in rats (Ueyama et al, 2011), and the exposure of C57BL/6 mice to low-frequency electromagnetic fields results in improvements in hippocampus neurogenesis (Cuccurazzu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%